2001
DOI: 10.1016/s0042-6989(00)00219-4
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous near-infrared spectroscopy monitoring of left and right occipital areas reveals contra-lateral hemodynamic changes upon hemi-field paradigm

Abstract: In this study we have shown that in humans it is possible to monitor non-invasively and simultaneously both hemispheres revealing cortical oxygenation changes in the occipital area in response to a contra-lateral hemi-field paradigm. A novel multi-channel near infrared spectroscopy approach with a high temporal resolution was used. The results confirm previous findings obtained by functional magnetic resonance imaging and positron emission tomography with the advantage to measure directly not only concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 41 publications
5
30
0
Order By: Relevance
“…It is notable that a similar left-sided lateralization of hemodynamic responses was noticed by Seiyama et al in their study of human visual cortex activation by NIR topography (Seiyama et al, 2004). In their spectroscopic study Colier et al (2001) obtained statistically significant responses in both sides of the visual cortex: however, the magnitudes of the changes in both [HbO 2 ] and [HHb] were significantly larger on the left side than on the right. Studying relationships between language dominance and asymmetries in the human brain using structural MR, Charles et al (1994) found that the asymmetry of the occipital lobe length was related to language dominance.…”
Section: Discussionsupporting
confidence: 76%
“…It is notable that a similar left-sided lateralization of hemodynamic responses was noticed by Seiyama et al in their study of human visual cortex activation by NIR topography (Seiyama et al, 2004). In their spectroscopic study Colier et al (2001) obtained statistically significant responses in both sides of the visual cortex: however, the magnitudes of the changes in both [HbO 2 ] and [HHb] were significantly larger on the left side than on the right. Studying relationships between language dominance and asymmetries in the human brain using structural MR, Charles et al (1994) found that the asymmetry of the occipital lobe length was related to language dominance.…”
Section: Discussionsupporting
confidence: 76%
“…Various stimuli were used in previous NIRS studies on visual brain function in adults, including picture observation [Villringer et al, 1993], flashing light at a frequency of 8 Hz [Kato et al, 1993], a multicolored moving dodecahedron [Wenzel et al, 1996], a green-red checkerboard reversing at a frequency of 10 Hz [Heekeren et al, 1999], a checkerboard [Takahashi et al, 2000], and a hemi-field green-white checkerboard reversing at a frequency of 8 Hz [Colier et al, 2001]. Results of those studies showed that the typical response of visual cortex activation in adults is an increase in [oxyHb] and a slight decrease in [deoxyHb].…”
Section: Discussionmentioning
confidence: 99%
“…6,7,29,30 It takes approximately the same amount of time for HbD levels to decrease in the visual cortex. Once the stimulus ends, approximately 10 to 12 s are needed for HbO and HbD to return to normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…Once the stimulus ends, approximately 10 to 12 s are needed for HbO and HbD to return to normal levels. 7,29,31 The time to reach an HbO maximum varies with the stimulus protocol used. For a 10-s on protocol, such as the one used in this study, a maximum occurs 1 to 2 s after the stimulus ends 29 before values begin returning to baseline.…”
Section: Discussionmentioning
confidence: 99%